Drop App: give voice to youngsters through new technologies to fight drop-out - Margarita Gandullo Recio (Centro de Estudios Financieros, 2016)
IES Valle de Aller is part of a european project Erasmus+ KA2 cooperation and innovation of good practices. IES Valle de Aller is working together on this project with other educational organizations from different European countries. In 2012, early school leavers (ESL) affects 5,500,000 young europeans aged between 18 and 24 years, either because they had not completed compulsory secondary education or because they did not follow higher education studies, both high school and vocational training. They were not in the labor market. The objective of the EU2020 is to reduce the rate of ESL by 10 %. All inquiries about so far show that ESL is caused by a mixture of individual circumstances, educational and socioeconomic conditions. In the last five years we have developed many educational interventions by the different national systems and regional educational policies to curb the rate of ESL. What is innovative in this project, and that means added value, is the fact that the approach is focused on finding the student in his own world. Young people between 14 and 18 would be much more motivated to continue education programs if they use the languages of the new information and communications technology (ICT), because they are really the digital natives.